Synthesis and Bacterial Evaluation of The V(IV), Cr(III), Fe(III) and Co(II) Ions Complexes with Mixed Ligands (2-hydroxybenzaldine)-4- Aminoantipyrine and 8-Hydroxyquinoline - Ibraheem, Israa H; Alias, Mahasin F; Ali, Doaa U (Al-Nahrain Journal of Science, 2018)
The primary ligand (2-hydroxybenzaldine)-4-aminoantipyrine (L)was prepared as achelating ligand, Which was treated with V(IV), Cr(III), Fe(III) and Co(II) ions in alcoholic medium in order to prepare series of new metal complexes in the presence of the Co-ligand 8-hydroxyquinoline.These complexes were prepared by convential method and characterized by available techniques, FT-IR, UV-Visible, magnetic susceptibility, flame atomic absorption technique as well as elemental analysis and conductivity measurements. From these studiesmeasurements, asquare pyramidal structure proposed for V(IV) while octahedral geometry for Cr(III), Fe(III) and Co(II) complexes. Thebacterial activity of the prepared complexes have been determine and compared with the ligands.